Contextualizing Socio-Technical Design of Accounting Information Systems: Evidence from a Digital Startup in Indonesia’s Sharing Economy - Ekasari, Kurnia; Afandi, Aang; Frantika, Shintiya Yulia (Journal of Applied Business, Taxation and Economics Research, 2026)
This study designs a socio-technical accounting information system (AIS) for a digital startup operating within Indonesia’s sharing economy. It aims to align technological components with organizational routines, human interactions, and the performance-based payroll structure used by online media platforms. Using the ADDIE development framework—Analyze, Design, Develop, Implement, and Evaluate—this research collects primary data through interviews and observations, supported by secondary company records. The system is developed into a contextualized AIS prototype that integrates socio-technical systems (STS) principles to ensure real-time revenue tracking, transparent payroll calculations, and improved coordination among the startup, its technology provider, and content creators. The results show that combining STS with ADDIE produces a flexible and human-centered AIS that supports performance-based compensation and collaborative digital workflows. This study offers originality by addressing the limited AIS design research for sharing economy-based digital startups in emerging economies, particularly in online media contexts. The findings provide practical implications for startups seeking adaptive, transparent, and resource-efficient financial systems aligned with decentralized business models.